Accelerating The Achievement of Badung Regency's Hotel Tax Target - Gede Risna Raditya Kusuma (Devotion : Journal of Research and Community Service, 2026)
This policy paper analyzed the gap between hotel tax targets and realizations in Badung Regency during the 2021–2025 period and formulated acceleration strategies to minimize the realization deficit in the hotel tax sector, which serves as a key contributor to Pendapatan Asli Daerah (PAD) or Regional Original Revenue. The study employed a qualitative methodology using a literature review approach and secondary data analysis derived from hotel tax realization reports from the Badung Regency Regional Revenue Office and the Badung Regent Accountability Reports (Laporan Keterangan Pertanggungjawaban [LKPJ]) for 2021–2025. Data analysis was conducted using a comparative descriptive approach to evaluate achievement levels against targets, identify fluctuation patterns and deviations, and formulate alternative policies. These alternatives were subsequently evaluated using a scoring method based on effectiveness, efficiency, and impact criteria. The results revealed significant fluctuations in hotel tax realization during 2021–2025, with the highest achievement of 140.2% recorded in 2022 and the lowest achievement of 35.0% in 2021. In 2023, the achievement rate reached 92.0% but declined again in 2024 and 2025 to 75.92% and 63.24%, respectively. These fluctuations were influenced by seasonal variations in tourist arrivals, hotel occupancy rates, the impact of the COVID-19 pandemic, taxpayer compliance, and challenges related to Online Travel Agent (OTA) transactions and unregistered accommodations, such as villas and boarding houses. Based on the analysis, six alternative policies were formulated. The Strengthening and Expansion of Web Service Systems alternative received the highest score of 4.67 and was selected as the primary policy, followed by the Simple E-Billing Application (4.33) and Tempat Objek Pajak Daerah (TOPD) Optimization (4.00) as complementary policies.